Efect Of Training Among Academic Staffs. - Ai, Yeow Jian (2006)
This research aims to positively identify the factors and variables involved in the interaction .The main objective is to identify the factors and variables involved in the interaction. The main objeective is to identify the effect of training among acadenic staffs in private colleges/institution.